Kaposi's sarcoma complicating long-term corticotherapy for rheumatoid arthritis - Sara Elloudi; Hakima Elmahi; Salim Gallouj; Fatima Zahra Mernissi (Our Dermatology Online, 2017)
Kaposi's sarcoma (KS) is a lymphoangioproliferative neoplasm induced by human herpes virus 8 (HHV-8). KS caused by iatrogenic immunosuppression is rare. Iatrogenic KS can present a therapeutic dilemma, as decreasing the level of immunosuppression may not be possible or may come at the high cost of organ rejection, such as in the case of organ transplant recipients or organ damage in the case of patients with autoimmune disorders. We report a new case of Kaposi's sarcoma induced by corticosteroids.